Mange in Companion Animals - Emma N. I. Weeks; Phillip E. Kaufman (EDIS)
Mange is a persistent skin condition of mammals caused by infestation with parasitic mites. Mites are tiny arthropods, usually less than 1 mm in length and difficult to see with the naked eye. Adult mites have eight legs, and larvae have six. The effect of the mites on the animal’s skin, called “mange,” is the most visible sign of an infestation. This 6-page fact sheet describes several skin conditions commonly caused by parasitic mites in domestic animals. Written by E. N. I. Weeks and P. E. Kaufman, and published by the UF Department of Entomology and Nematology, September 2012.